Sustainable Development, Environmental Planning, and People's Initiative - Ragragio, Conchita M. (Kasarinlan: Philippine Journal of Third World Studies; Vol 9 No 1 (1993): Philippine Environmental Politics, 2008)
The paper discusses sustainable development and its various definitions and applications. At present, sustainable development has become a regular component in development plans of governments and private enterprises. In order for sustainable development to be successful, it needs to implement a new set of global ethics that stresses the preservation of environment. As natural resources are inextricably linked with development, environmental planning is crucial in managing, maximizing, and securing the preservations of natural resources. Such objectives are seen in the framework of environmental planning. To ground and delimit the discussion, a historical survey and elucidation of environmental planning policies in the context of Philippine setting followed. Since there is a need to involve all sectors in the planning, decision-making, and utilization of natural resources, various points of intervention through people’s initiatives emphasizing the 1991 Local Government Code (LGC) as a point of active intervention are discussed. Ultimately, the paper posits that planning, decision-making, and utilization of resources cannot stand on its own and must be strategically and carefully handled in order for its sound and relevant implementation.
Keywords: Sustainable development, Environment Planning, People’s initiatives